2016
DOI: 10.1007/s10103-016-2071-z
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy (PBMT) and/or cryotherapy in skeletal muscle restitution, what is better? A randomized, double-blinded, placebo-controlled clinical trial

Abstract: Cryotherapy for post-exercise recovery remains widely used despite the lack of quality evidence. Photobiomodulation therapy (PBMT) studies (with both low-level laser therapy and light-emitting diode therapy) have demonstrated positive scientific evidence to suggest its use. The study aims to evaluate PBMT and cryotherapy as a single or combined treatment on skeletal muscle recovery after eccentric contractions of knee extensors. Fifty healthy male volunteers were recruited and randomized into five groups (PBMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 35 publications
2
38
1
2
Order By: Relevance
“…[4][5][6][7][8] There were no studies found in the literature search that supported cryotherapy over PBMT. The PBMT was more effective in preventing increases in CK levels, 4-8 blood lactate, 5 C-reactive protein, 5,7 and inflammation 6,7 after an exercise bout.…”
Section: Best Evidencementioning
confidence: 83%
See 4 more Smart Citations
“…[4][5][6][7][8] There were no studies found in the literature search that supported cryotherapy over PBMT. The PBMT was more effective in preventing increases in CK levels, 4-8 blood lactate, 5 C-reactive protein, 5,7 and inflammation 6,7 after an exercise bout.…”
Section: Best Evidencementioning
confidence: 83%
“…12,25 Muscle damage was noted in the included studies following the exercise protocols. This was demonstrated by an increase of CK, blood lactate, and frequency of necrosis, measured by histological analysis, in placebo treatments, 4,5,8 an ice bag application, 4,8 and coldwater immersion therapy. 5,7 Compared with placebo treated groups, cryotherapy demonstrated no difference in CK 4,5,8 or blood lactate 5 levels at any time points.…”
Section: Best Evidencementioning
confidence: 99%
See 3 more Smart Citations